سیرت طیبہ کی تشریعیاتی حیثیت کا تحقیقی و تاریخی مطالعہ: A Research review of the legislative Status of the Sirah of Holy Prophet ﷺ - Fareed ud din, Hafiz (Al-Amīr Research Journal for Islamic Studies, 2020)
The deeds and actions of the Holy Prophet ﷺ is a practical interpretation of the Holy Qur’an. Allah Almighty has stated his Shari’ah in short but comprehensive words that “take what the Holy Prophet ﷺ has given you and which you forbid”. Therefore, his command is the command of Allah Almighty and not yours. That is why the Holy Qur’an has declared his obedience to be the obedience of Allah Almighty. And from the instructions of the selected scholars of the ummah, it is clear that the legislative status of The Sirah is authenticated. Allah Almighty has given him a special position of Shariah. As for the legislative status of Sira-e-Taiba, both the special and the general legislation are specific or special to him. Special legislation etc i.e. you have legislated for a specific person at certain times like accepting the condition of a person that he will convert to Islam if he prays only two prayers. The other person cannot join. The general legislation in which you have enacted all kinds of legislation for the common ummah is included. The center and axis of Islamic law is your caste. You have complete control over the status and sanctity, likes and dislikes as you like, for whom you can make Shariah whenever you want. It is as if you are a follower of the Shari’ah. He also has full authority in the brief description of the Qur’an, in the adherence to the Absolute, and the explanation of similarities. You are authorized to legislate as a Shari’ah and Shari’ah in all areas of worship, affairs, debates, and crimes. Therefore, in this article, the legislative status of His Sira-e-Taiba has been explained in the light of Qur’an and Hadith, Sahabah and Tabi’een, and the commandments of Imams and jurists.